Effects of Concurrent Training and Intermittent Fasting on Structural, Functional, and Morphological Parameters of the Heart - Marcelo, Henrique Izaias; Aleixo, Paulo Henrique [UNESP]; Da Silva, Rafael Pereira [UNESP]; Pacagnelli, Francis Lopes; Brinholi Victorino Da Silva, Rejane Batista; Silva Camargo Filho, Jose Carlos [UNESP]; Carvalho Zanuto, Everton Alex; Castoldi, Robson Chacon [UNESP] (Soc Chilena Anatomia, 2021)
Intermittent fasting and concurrent training have been performed frequently to decrease body mass. The aim was to analyze the effects of concurrent training (CT) and intermittent fasting (IF) on cardiac remodeling. In total, 39 adult male Wistar rats were used, divided into four groups: control (C [n = 12]), fasting control (FC [n = 11]), training (T [n = 8]) and fasting training (FT [n = 8]).The CT protocol was composed of 12 sessions, with 30 minutes of aerobic training (AT) in the liquid medium at an intensity of 80 % of the anaerobic threshold, followed by resistance training (RT) with 4 series of 10 aquatic jumps at an corresponding to 50 % of body weight. The IF period was established at 12/12 hours, starting at 9 p.m. and ending at 9 a.m. Echocardiographic analyzes were performed before and after the intervention and, at the end of the experiment, samples of the cardiac tissue were collected to perform the histological analyses. Data analysis was performed using the Shapiro-Wilk tests, Analysis of Variance -ANOVA with Tukey's post-test, and Kruskal-Wallis with Dunn's post-test. All procedures assumed an error of 5 % (p<0.05). Neither group showed alterations in the functional (min. p= 0.12 -max. p= 0.83) and structural parameters of the heart (min. p=0.31 -max. p=0.83). A decrease was observed in the area of cardiomyocytes in the T (p=0.001) and FT groups (p=0.001). The CT and IF did not alter the functional and structural parameters of the heart, but did cause a decrease in the area of the cardiomyocytes.
Keywords: Histology; Cardiology; Heart; Rats; Exercise